2011
DOI: 10.1016/j.biologicals.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Quality, safety and efficacy of follow-on biologics in Japan

Abstract: Recently, WHO, EU, Japan and Canada have published guidelines on biosimilar/follow-on biologics. While there seems to be no significant difference in the general concept in these guidelines, the data to be submitted for product approval are partially different. Differences have been noted in the requirements for comparability studies on stability, prerequisites for reference product, or for the need of comparability exercise for determination of process-related impurities. In Japan, there have been many discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 2 publications
0
23
0
1
Order By: Relevance
“…As noted by Yamaguchi and colleagues, 3 and in the country-by-country descriptions of regulatory requirements included in table 1 of our Review, 1 Japan’s PDMA requires that sponsors show similarity between a biosimilar candidate and the reference product through clinical and non-clinical studies, and structural and functional analyses. However, in some instances, formal comparative efficacy studies might not be required.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…As noted by Yamaguchi and colleagues, 3 and in the country-by-country descriptions of regulatory requirements included in table 1 of our Review, 1 Japan’s PDMA requires that sponsors show similarity between a biosimilar candidate and the reference product through clinical and non-clinical studies, and structural and functional analyses. However, in some instances, formal comparative efficacy studies might not be required.…”
mentioning
confidence: 86%
“…The English-language literature published before our Review’s cutoff point of Oct 30, 2014, for our review identified epoetin as the only biosimilar that had received regulatory approval from Japan’s Pharmaceuticals and Medical Device Agency (PDMA); however, as noted by Nagai and colleagues, epoetin was not approved for indications related to chemotherapy. 2,3 English-language descriptions of subsequently approved oncology biosimilars in Japan (all filgrastims) were published after our literature cutoff. 4 Somatotropin received PDMA approval in 2009; however, it is not an oncology biosimilar.…”
mentioning
confidence: 99%
“…In 2010, PDMA approved a biosimilar epoetin, although its indication does not include oncology; no oncology biosimilar has yet received PDMA approval. 29 …”
Section: Regulationsmentioning
confidence: 99%
“…The necessary tests can cover quality, pharmacology, toxicity, pharmacokinetic, pharmacodynamic, and clinical safety (e.g. immunogenicity) and effi cacy [5].…”
Section: Generic Drugs and Biosimilarsmentioning
confidence: 99%
“…The necessary tests can cover quality, pharmacology, toxicity, pharmacokinetic, pharmacodynamic, and clinical safety (e.g. immunogenicity) and effi cacy [5].Until Spring 2012, MHLW/PMDA has approved two biosimilars: somatropin and epoetin alpha, both in 2009 [6][7][8]. …”
mentioning
confidence: 99%